2011
DOI: 10.4149/neo_2011_05_392
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of CHEK2 forkhead-associated domain increase the risk of Hodgkin lymphoma

Abstract: Checkpoint kinase 2 gene (CHEK2) codes for an important mediator of DNA damage response pathway. Mutations in the CHEK2 gene increase the risk of several cancer types, however, their role in Hodgkin lymphoma (HL) has not been studied so far. The most frequent CHEK2 alterations (including c.470T>C; p.I157T) cluster into the forkhead-associated (FHA) domaincoding region of the CHEK2 gene. We performed mutation analysis of the CHEK2 gene segment coding for FHA domain using denaturing high-performance liquid chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Also carriers reported more frequently family history of thyroid cancer, prostate cancer and endometrial cancer. These results further support that CHEK2 is a cancer susceptibility gene associated with increased risk of cancer at several different sites, including breast, prostate, thyroid, colon, kidney, stomach, (low‐grade) ovarian, bladder, chronic lymphocytic leukemia, Hodgkin lymphoma and a reduced risk of other cancers (lung and laryngeal cancer) . The current study suggests that the risk of sarcoma and non‐Hodgkin lymphoma may also be increased.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Also carriers reported more frequently family history of thyroid cancer, prostate cancer and endometrial cancer. These results further support that CHEK2 is a cancer susceptibility gene associated with increased risk of cancer at several different sites, including breast, prostate, thyroid, colon, kidney, stomach, (low‐grade) ovarian, bladder, chronic lymphocytic leukemia, Hodgkin lymphoma and a reduced risk of other cancers (lung and laryngeal cancer) . The current study suggests that the risk of sarcoma and non‐Hodgkin lymphoma may also be increased.…”
Section: Discussionsupporting
confidence: 83%
“…These results further support that CHEK2 is a cancer susceptibility gene associated with increased risk of cancer at several different sites, including breast, prostate, thyroid, colon, kidney, stomach, (low-grade) ovarian, bladder, chronic lymphocytic leukemia, Hodgkin lymphoma and a reduced risk of other cancers (lung and laryngeal cancer). [30][31][32][33][34][35][36] The current study suggests that the risk of sarcoma and non-Hodgkin lymphoma may also be increased. Of note, CHEK2 mutations were first detected in patients with Li-Fraumeni type families, and in the original studies of CHEK2 mutations and Li-Fraumeni syndrome, cancers of the breast, colon, ovary, endometrium, kidney, stomach were reported.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies have revealed an association between the CHEK2 I157T variant and cancer susceptibility. However, the results were conflicting, including an increased risk (Cybulski et al, 2004a(Cybulski et al, , 2004b(Cybulski et al, , 2007a(Cybulski et al, , 2007bKilpivaara et al, 2004Kilpivaara et al, , 2006Bogdanova et al, 2005;Irmejs et al, 2006;Kleibl et al, 2009;Serrano-Fernandez et al, 2009;Havranek et al, 2011;Domagala et al, 2012), a reduced risk , and no association (Dufault et al, 2004;Debniak et al, 2008;Kleibl et al, 2008;Konstantinova et al, 2009Konstantinova et al, , 2010Mohelnikova-Duchonova et al, 2010;Bayram et al, 2012Bayram et al, , 2013.…”
Section: Introductionmentioning
confidence: 94%
“…Cell cycle checkpoint kinase 2 (CHEK2) has been identified as a type of serine/threonine protein kinase, located in chromosome 22 q12.1 of humans and yeast. It has been confirmed as an important mediator of the DNA damage response pathway, and as a susceptibility gene in several types of cancer (16,17). As a tumor suppressor gene, CHEK2 is vital for the induction of cell cycle arrest and cell apoptosis following DNA damage.…”
Section: Introductionmentioning
confidence: 99%